\(Δ^m\)-Ideal Convergence of Generalized Difference Sequences in Neutrosophic Normed Spaces - Kaur, Gursimran; Meenakshi , (Communications in Mathematics and Applications, 2022)
The objective of this paper is to introduce the perception of ideal convergence of generalized difference sequences in Neutrosophic Normed Spaces. We defined the concepts of \(Δ^m\)-\(I_N\)-Cauchy and \(Δ^m\)-\(I_N\)-completeness for generalized difference sequences in Neutrosophic Normed Spaces (briefly known as N.N.S). Another, closely related concept \(Δ^m\)-\(I_N^*\)-convergence, \(Δ^m\)-\(I_N^*\)-Cauchy and \(Δ^m\)-\(I_N^*\)-completeness in N.N.S are also defined. Later, we establish some relations among these perceptions which shows that this method of convergence is more generalized.